PERSEPSI MASYARAKAT TENTANG KEBIASAAN SUKU BATAK TOBA MENGKONSUMSI TUAK DI DESA LUMBAN PINGGOL KECAMATAN PANGURURAN KABUPATEN SAMOSIR PROVINSI SUMATERA UTARA - sitanggang, Apri ani; Hambali, Hambali; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine people's perceptions of the habits of theToba Batak tribe consuming Tuak. This research uses a qualitative approach. Theinformants who were examined using a purposive sampling technique were TuakDrinkers, No Drinkers, Mothers, Muslim Communities, Christian ReligiousCommunities, Village Heads, Lumban Pinggol Village Customary Leaders. Datacollection techniques used are Observation, Interview, Data Analysis. Based on theresults of research conducted, it can be concluded that public perception of the habits ofthe Batak tribe to consume tuak is a drink that can be used as medicine if consumed insmall portions, but many people consume in excessive portions, causing the condition ofa person (consuming) drunk. So that social deviations occur.Key Words: Community Perception, Consuming Tuak